The outbreak of dengue in recent years- an observational study performed at Mohammadpur Upazila Health Complex of Magura district, Bangladesh (Bangladesh Journal of Medicine, 2025)
Introduction: Dengue is an emerging arboviral infection caused by a flavivirus strain. All four serotypes are prevalent in Bangladesh. In 2023, Bangladesh experienced a severe upsurge of dengue, resulting in a high number of dengue-related deaths. Several factors are associated with the increasing risk of the spread of the dengue epidemic in Bangladesh.Methods: This is a single-center, descriptive observational study. A total of 940 confirmed dengue patients were considered the analytical sample for our study. The finalized data were imported into the statistical software (SPSS Version 25) for analysis and compared with clinical findings, measured BP level, IV fluid, antibiotic use, and outcome of the dengue patients.Results: In 2023, Bangladesh had the worst dengue outbreak including our study place. In our study center, in 2022 only 11 confirmed dengue cases were reported (0.2% of total admitted patients) and in 2024 the documented number was101(1.5% of total admitted patients) but in 2023 total of 1041 patients (14% of total admitted patients) were treated as dengue. A total of 940 admitted confirmed dengue cases were included in the study. Male patients supersede females in number. All patients were symptomatic and 6.7% had co-morbidities. Out of 940 patients; 83.5 %( 785) patients had dengue fever, 1.5 %( 13) had dengue hemorrhagic fever, and 15 %( 142) had dengue shock syndrome. Sex influences clinical severity though statistically not significant (p value=0.378). Most of the patients (64.1%) stayed less than 3 days in hospitals. A total of 8.6% (81) patients developed complications during inpatients. Most (94.8%) of the admitted dengue patients were treated with IV fluids (p value=0.01).Conclusion: In 2023 Bangladesh faced a severe and unexpected outbreak of dengue infection. Male and young patients were mostly affected by dengue infection. Though there have been a large number of deaths in recent years, most of the patients recovered uneventfully.Bangladesh J Medicine 2025; 36(2): 108-114